Phylogenetic Trends in the Dissymmetrisation of Genitalia in Hadenini (Lepidoptera, Noctuidae) - Zoltán Varga; Gábor Ronkay; László Ronkay (Diversity, 2024)
The external genital appendages of Noctuidae represent correlated–coevolved elements of a complex structure. The pathways of changes are delimited by some constraints, and they are parallelly evolved in different phyletic lines. Asymmetrical male external genitalia were found in Hadenini, in Polia and its closely related genera, but also in Anarta (s. l.). In Poliina, the asymmetry of the genital capsule is mostly expressed in the Holarctic Polia nebulosa species group, forming the basal split within Polia (s. str.). Higher species diversity, as a consequence of asymmetry connected with the split of functions between the right and left sides, was observed in Polia (s. str.) and in Anarta (s. l.). The highest level of expansivity was observed in the Holarctic Anarta, where some species are migrating and becoming invasive ones, while a bulk of species populates the steppic and mountainous habitats of North America and Central Asia. Parallelly, while some genera/subgenera of the subtribe Poliina are oligotypic and/or consist of strictly localised species, the sensu stricto Polia species with asymmetrical genital capsules are widely distributed. The diversification of the Hadulina phylogenetic line should have been initiated by the Messinian aridisation crisis. The core area of diversification of Poliina was connected with the Sino-Himalayan region, followed by expansion into the Holarctic boreo-nemoral zone.